The Use of Song Lyrics to Improve Students' Pronunciation in SMK Kristen Imanuel Laikit - Mokodompis, Daniel; Pelenkahu, Noldy; Hampp, Paula (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2024)
The background of this research was based on students’ difficulties in learning how to pronounce words and sentences. This research is intended to see whether or not learning with song and its lyrics is an effective way to improve students’ pronunciation. For that reason, a learning method was conducted in SMK Kristen Imanuel Laikit with the subject of the research was the 11th grader class consist of 15 students. This research intended to create an alternative method to improve the atmosphere of the teaching process so that the students were more comfortable and boost their spirit to learn even more. This research used a Classroom Action Research, a quantitative research approach. The implementation of learning with song and its lyrics was conducted with pre-test, treatment, post-test, and finally, for further calculated the data, SPSS 26 was used in this research. All 15 students were participated in both pre-test and post-test where the average of students’ pre-test score was 58.66%, and the average of post-test score after the treatment was used is 78.06%. by those results, the increase percentage was calculated and the results showed that the 11th grader of SMK Kristen Imanuel Laikit made an improvement score of 33.70%. from those results, this study can be concluded that the use of song and its lyrics can improve students’ pronunciation.